Lithium manganese iron phosphate composite positive electrode slurry and preparation method thereof, lithium manganese iron phosphate composite positive plate and lithium ion battery
By using the active substances, conductors and adhesives of specific combinations in the positive slurry of lithium manganese iron phosphate iron batteries, and use low -solid multi -step decentralized processes to solve the emergence of lithium manganese iron phosphate iron battery The problems such as gel, solid low and viscosity rebound have achieved higher electrochemical performance and energy density, while reducing costs.
Patent Information
- Application Number
- CN202411310081.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-28
AI Technical Summary
During the homogenization process, existing lithium manganese iron phosphate batteries are prone to problems such as gel, low solid content, and large viscosity rebound, resulting in low compaction of the electrode sheet and easy cracking, and poor cell circulation and high temperature performance.
Active substances including manganese iron phosphate iron and ternary materials, conductive conductives with conductive carbon black SP and multi -wall carbon nanotubes, PVDF adhesives with different molecular weights, and composite composite of polymer polymer dispersion with anchor groups The positive pulp is evenly pulled through the low -fixed multi -step dispersion process.
Improve the stability of the uniform slurry of manganese iron lithium -lithium composite positive pulp and the compact density of the polar tension, improve the electrochemical performance and energy density, and reduce the cost.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a manganese iron phosphate lithium composite positive electrode slurry and a preparation method thereof, a manganese iron phosphate lithium composite positive electrode sheet and a lithium ion battery. Background Art
[0002] At present, the power batteries used in new energy vehicles commonly seen on the market are almost all ternary and lithium iron phosphate power batteries. Lithium iron phosphate batteries are famous for their safety, but their low energy density means that they cannot dominate the market. Ternary batteries have become the first choice for some high-end models due to their ultra-high energy density, but their safety performance is daunting; especially the frequent fire accidents caused by batteries in new energy vehicles on the market have attracted people's attention to the safety performance of new energy vehicles. Lithium iron manganese phosphate and lithium iron phosphate have the same olivine structure, stable material structure, and a voltage platform comparable to ternary, which also means higher energy density. It can be said that it has both the safety performance of lithium iron phosphate and the high energy density of ternary. In the future, there may be an opportunity to form a three-way situation with lithium iron phosphate and ternary in the new energy power battery market.
[0003] The existing lithium iron phosphate and ternary systems have relatively mature formulas and homogenization processes, and both processing performance and battery electrical performance are relatively good. Due to its special material properties, nano-level small particle size and low conductivity, lithium manganese iron phosphate materials are prone to gelation, low solid content, and large viscosity rebound during the homogenization process. At the same time, the subsequent prepared pole pieces have low compaction and are prone to cracking, resulting in poor cycle performance and high temperature performance of the battery cells.
[0004] There are also reports on the slurry formula and preparation method of lithium iron manganese phosphate in the prior art. For example, CN116960282A provides a formula of lithium iron manganese phosphate mixed with high-nickel ternary material positive electrode slurry and its homogenization method. The formula is doped with a large amount of high-nickel ternary material, and the mixing ratio of lithium iron manganese phosphate is only 10-50%. It is essentially a ternary battery, not a lithium iron manganese phosphate battery. The stirring process with high solid content of the slurry is adopted. This method is easy to wear the equipment, easy to introduce metal impurities, easy to damage the binder, and difficult to disperse the conductive glue. At the same time, the cost of the battery made by this system is also relatively high, which does not reflect the cost advantage. The safety performance has not been tested and is expected to be equivalent to the ternary. For another example, CN117199364A adopts the method of doping ternary and lithium manganate, with 60-75 parts of nickel cobalt lithium manganese, 5-30 parts of lithium iron manganese phosphate, and 5-30 parts of lithium manganese. Similarly, the mixing ratio of lithium iron manganese phosphate in this method is only a minority, and the ternary is the vast majority, which is essentially a ternary battery. The homogenization method is also relatively rough. All materials are mixed in one pot, the dispersion performance of the materials is poor, and a good stirring effect cannot be achieved. In addition, the introduced lithium manganese oxide and lithium iron manganese phosphate have the same low conductivity and poor high-temperature performance, which affects the electrical performance advantages of lithium iron manganese phosphate materials, and the material cost is also relatively high.
[0005] In general, the existing technology only improves the performance of one parameter of lithium manganese iron phosphate, without comprehensively considering other performance parameters, and can only achieve partial optimization results. Therefore, it is urgent to provide a comprehensive technical solution with stable slurry, superior electrical performance and low cost.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] In view of the shortcomings and defects of the prior art, the present invention aims to provide a lithium iron manganese phosphate composite positive electrode slurry and a preparation method thereof, a lithium iron manganese phosphate composite positive electrode sheet and a lithium ion battery.
[0008] In order to achieve the above purpose, the following technical solutions are adopted:
[0009] The first object of the present invention is to provide a lithium manganese iron phosphate composite positive electrode slurry, comprising the following raw materials: an active material, a conductive agent, a binder, a dispersant and a solvent;
[0010] The active material includes lithium manganese iron phosphate and ternary material, and the mass ratio of lithium manganese iron phosphate to the ternary material is (7-9): (3-1);
[0011] The conductive agent includes conductive carbon black SP and multi-walled carbon nanotubes;
[0012] The binder includes a PVDF binder A with a molecular weight of 600,000-800,000 and a PVDF binder B with a molecular weight of 900,000-1.2 million;
[0013] The dispersant includes a high molecular weight polymer having an anchoring group and a soluble long chain structure.
[0014] Further, based on the above technical solution of the present invention, the mass ratio of the conductive carbon black SP and the multi-walled carbon nanotubes in the conductive agent is (1-2): (0.5-1);
[0015] And / or, the multi-walled carbon nanotubes are graphene-doped multi-walled carbon nanotube slurry;
[0016] And / or, the mass ratio of PVDF binder A to PVDF binder B in the binder is (3-1):(1-3).
[0017] Further, on the basis of the above technical solution of the present invention, the anchoring group in the dispersant comprises at least one of a hydroxyl group, a carboxylic acid group, an amino group, an amide group and a phosphate group;
[0018] And / or, the soluble long chains in the dispersant include polyester soluble long chains.
[0019] Further, on the basis of the above technical solution of the present invention, the ternary material includes high nickel polycrystalline eight-series NCM and nine-series NCM;
[0020] and / or, the solvent comprises N-methylpyrrolidone;
[0021] And / or, the mass ratio of the active material, conductive agent, binder, dispersant and solvent is (95-97): (1.5-2.5): (1.5-2.5): (0.1-0.2): (50-65).
[0022] The second object of the present invention is to provide a method for preparing the above-mentioned lithium manganese iron phosphate composite positive electrode slurry, comprising the following steps:
[0023] (a) mixing and dispersing a binder and a solvent to obtain a mixed glue solution;
[0024] (b) adding a conductive agent and a dispersant to the mixed adhesive solution and mixing and dispersing the mixed adhesive solution to obtain a conductive adhesive solution;
[0025] (c) adding an active material formed by mixing lithium manganese iron phosphate and a ternary material into the conductive glue to mix and disperse the mixture, thereby obtaining a lithium manganese iron phosphate composite positive electrode slurry.
[0026] Further, based on the above technical solution of the present invention, in step (a), the binder and the solvent are first stirred and mixed at a low speed, and then dispersed at a high speed to obtain a mixed glue solution;
[0027] Preferably, in step (a), the stirring speed of the low-speed stirring and mixing is 20-40 rpm, the stirring time is 5-15 min, and the dispersion linear speed of the high-speed dispersion is 12-18 m / s, and the dispersion time is 2.5-3.5 h;
[0028] Preferably, in step (a), the solid content of the mixed glue solution is 4-8%.
[0029] Further, on the basis of the above technical solution of the present invention, in step (b), a conductive agent and a dispersant are added to the mixed glue solution, first stirred and mixed at a low speed, and then dispersed at a high speed to obtain a conductive glue solution;
[0030] Preferably, in step (b), the stirring speed of the low-speed stirring and mixing is 20-40 rpm, the stirring time is 5-15 min, and the dispersion linear speed of the high-speed dispersion is 12-18 m / s, and the dispersion time is 0.5-1.5 h;
[0031] Preferably, in step (b), the solid content of the conductive adhesive is 7-10%.
[0032] Further, on the basis of the above technical solution of the present invention, in step (c), the active material formed by mixing lithium manganese iron phosphate and the ternary material is added to the conductive glue solution, first stirred and mixed at a low speed, and then dispersed at a high speed;
[0033] Preferably, in step (c), the stirring speed of the low-speed stirring and mixing is 20-40 rpm, the stirring time is 5-15 min, and the dispersion linear speed of the high-speed dispersion is 12-18 m / s, and the dispersion time is 2-3 h.
[0034] The third object of the present invention is to provide a lithium manganese iron phosphate composite positive electrode sheet, comprising a current collector and an active coating disposed on the surface of the current collector;
[0035] The active coating is made of the lithium iron manganese phosphate composite positive electrode slurry provided by the first purpose of the present invention or the lithium iron manganese phosphate composite positive electrode slurry prepared by the preparation method provided by the second purpose of the present invention.
[0036] The fourth object of the present invention is to provide a lithium-ion battery, comprising the lithium manganese iron phosphate composite positive electrode sheet provided by the third object of the present invention.
[0037] Compared with the prior art, the technical solution of the present invention has at least the following technical effects:
[0038] (1) The present invention provides a lithium iron phosphate composite positive electrode slurry, which is mainly made of active material, conductive agent, binder, dispersant and solvent; wherein the active material is lithium iron manganese phosphate mixed with a small proportion of ternary material, which can achieve the effect of doping large and small particles, avoid the agglomeration of small particles (lithium iron manganese phosphate), and improve the problem of easy gelation of the slurry and low solid content, that is, while improving the slurry processing performance, it also increases the compaction density of the pole piece, which is beneficial to the improvement of electrochemical performance and energy density; the binder is compounded with two PVDFs with different molecular weights, which can improve the poor adhesion of a single low molecular weight PVDF and the poor anti-gelation properties of a single high molecular weight PVDF, avoid the viscosity rebound of the positive electrode slurry, and further improve the poor peeling force of the pole piece and the cracking problem of the pole piece coating to a large extent; the dispersant is a dispersant with a specific group and structure, which is better than the traditional polyvinyl pyrrolidone dispersant in improving the slurry gel and pole piece cracking, and can further improve the softness of the pole piece and reduce the cost.
[0039] (2) The present invention provides a method for preparing the above-mentioned lithium iron phosphate composite material, which adopts a low-solid multi-step dispersion process to avoid the high-solid kneading step. During the homogenization process, the solid content of the added slurry is controlled to ensure the uniform dispersion of each component, while avoiding the wear of the high-solid slurry on the equipment and the introduction of metal foreign matter.
[0040] (3) The present invention provides a lithium iron manganese phosphate composite positive electrode sheet, which is made using the lithium iron manganese phosphate composite positive electrode slurry provided by the present invention; in view of the advantages of the lithium iron manganese phosphate composite positive electrode slurry, the positive electrode sheet made therefrom has good softness, high compaction density and peel strength, and low membrane resistance.
[0041] (4) The present invention provides a lithium-ion battery comprising the above-mentioned lithium iron phosphate composite positive electrode sheet; in view of the advantages of the above-mentioned lithium iron manganese phosphate composite positive electrode sheet of the present invention, the lithium-ion battery comprising it has better electrochemical performance. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0043] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0044] According to a first aspect of the present invention, there is provided a lithium manganese iron phosphate composite positive electrode slurry, comprising the following raw materials: an active material, a conductive agent, a binder, a dispersant and a solvent;
[0045] The active material includes lithium manganese iron phosphate and ternary material, and the mass ratio of lithium manganese iron phosphate to the ternary material is (7-9): (3-1);
[0046] The conductive agent includes conductive carbon black SP and multi-walled carbon nanotubes;
[0047] The binder includes a PVDF binder A with a molecular weight of 600,000-800,000 and a PVDF binder B with a molecular weight of 900,000-1.2 million;
[0048] The dispersant includes a high molecular weight polymer having an anchoring group and a soluble long chain structure.
[0049] Specifically, in the lithium iron manganese phosphate composite positive electrode slurry provided by the present invention, the active material used is mainly lithium iron manganese phosphate and a small amount of ternary materials are compounded. Compared with the prior art solution that dopes a large proportion of ternary materials or lithium manganate, the present invention dopes a small proportion of ternary materials into lithium iron manganese phosphate, which can achieve the effect of doping large and small particles, avoid the agglomeration of small particles (lithium iron manganese phosphate), and improve the problem of easy gelation of homogenate and low solid content, that is, while improving the homogenate processing performance, it also increases the compaction density of the pole piece, which is conducive to the improvement of electrochemical performance and energy density. There are certain restrictions on the mass ratio of lithium iron manganese phosphate and ternary materials in the active material. If the mass ratio of lithium iron manganese phosphate and ternary materials in the active material is too low (lower than 7:3), the proportion of ternary materials increases, which is likely to lead to improved processing performance, but the safety performance of the obtained battery will decrease, and the cost will increase. If the mass ratio of lithium iron manganese phosphate and ternary materials in the active material is too high (higher than 9:1), the proportion of lithium iron manganese phosphate increases, which is likely to lead to poor processing performance, reduced yield, and weakened energy density and performance of the obtained product. Therefore, the typical but non-restrictive mass ratio of lithium iron manganese phosphate and ternary materials is 7:3, 7:2, 7:1, 8:3, 8:2, 8:1, 9:3, 9:2 or 9:1, etc.
[0050] In the prior art, a single PVDF is usually used as a binder. However, the present invention takes into account the problems of easy agglomeration, easy gelation and poor peeling strength of lithium manganese iron phosphate, and deliberately selects two specific types of PVDF binders for compounding. PVDF binder A with a molecular weight of 600,000-800,000 (for example, 600,000, 700,000 or 800,000, etc.) is easier to disperse and has a good anti-gel effect, but the adhesive prepared with the same ratio is worse; PVDF binder B with a molecular weight of 900,000-1.2 million (for example, 900,000, 1 million, 1.1 million or 1.2 million, etc.) has a better adhesive strength when prepared with the same ratio, but it is more difficult to disperse and easy to gel. Therefore, compounding and regulating the two can improve the poor adhesion of a single low molecular weight PVDF and the poor anti-gel properties of a single high molecular weight PVDF, avoid the viscosity rebound of the positive electrode slurry, and thus can greatly improve the poor peeling strength of the pole piece and the cracking of the pole piece coating. On the other hand, compounding the two binders can improve the bonding strength and reduce the amount of binder used, thereby appropriately increasing the load of the main material, and can also optimize the dispersion effect of lithium manganese iron phosphate to a certain extent.
[0051] Different from the prior art, the present invention uses conductive carbon black SP and multi-walled carbon nanotubes with a slightly lower price as conductive agents. Conductive carbon black SP is granular, and carbon nanotubes are "linear". The use of two different forms of conductive agents for compounding can improve the conductivity of the positive electrode slurry, improve the flexibility of the electrode sheet, and reduce costs.
[0052] In the prior art, polyvinyl pyrrolidone (PVP) is usually added as a dispersant for the slurry, while in the present invention, a new type of long-chain molecule containing multiple anchoring groups is used to improve the dispersion effect and stability of the active substance in the positive electrode slurry, and the addition amount is smaller, which has a better effect on improving the slurry gel and the cracking of the pole piece, and can further improve the flexibility of the pole piece and reduce the cost. At the same time, PVP is easy to decompose and produce gas under high temperature and high pressure, and its structure is unstable, while the dispersant used in the present invention has a stable structure and a high redox potential.
[0053] As an optional embodiment of the present invention, the mass ratio of PVDF binder A to PVDF binder B in the binder is (3-1):(1-3), and a typical but non-limiting mass ratio is 3:1, 2:1, 1:1, 1:2, 1:3, 2:3, etc.
[0054] By further limiting the mass ratio of PVDF binder A to PVDF binder B, it is possible to meet the bonding strength requirement with a small addition amount while avoiding homogenous gelation.
[0055] As an optional embodiment of the present invention, the multi-walled carbon nanotubes are graphene-doped multi-walled carbon nanotube slurry.
[0056] Multi-walled carbon nanotubes doped with a small amount of graphene are compounded with conductive carbon black SP, so that the conductive contact surface has a multi-conductive contact mode of points, points and lines, points and surfaces, and lines and surfaces, which ensures the conductive performance, increases the conductive effect and improves the softness of the electrode.
[0057] As an optional embodiment of the present invention, the mass ratio of the conductive carbon black SP to the multi-walled carbon nanotubes in the conductive agent is (1-2): (0.5-1). Typical but non-limiting mass ratios are 1:0.5, 1.2:0.5, 1.5:0.5, 1.6:0.5, 1.8:0.5, 2:0.5, 1:0.8, 1.5:0.8, 2:0.8, 1:1, 1.2:1, 1.5:1 or 2:1, etc.
[0058] As an optional embodiment of the present invention, the anchoring group in the dispersant comprises at least one of a hydroxyl group, a carboxylic acid group, an amino group, an amide group and a phosphate group. The above anchoring group has a coordination effect with Fe and can be adsorbed on the non-polar carbon surface.
[0059] As an optional embodiment of the present invention, the soluble long chain in the dispersant includes a polyester soluble long chain.
[0060] The specific brand of the dispersant is not limited. Generally speaking, as long as the dispersant contains the above-mentioned specific anchoring group and a soluble long-chain structure, a good effect can be achieved. Typical but non-limiting dispersants include dispersants with brands of Haofei HFF2968, Haofei HFF2928, and Haofei HFF2918.
[0061] As an optional embodiment of the present invention, the ternary material includes high-nickel polycrystalline eight-series NCM and nine-series NCM.
[0062] As an optional embodiment of the present invention, the solvent includes N-methylpyrrolidone (NMP).
[0063] As an optional embodiment of the present invention, the mass ratio of active material, conductive agent, binder, dispersant and solvent is (95-97): (1.5-2.5): (1.5-2.5): (0.1-0.2): (50-65). Typical but non-limiting mass ratios of active material, conductive agent, binder, dispersant and solvent are 95: 2.5: 2.4: 0.1: 50, 96: 1.9: 2.0: 0.1: 50, 96: 1.9: 2.0: 0.1: 60, 96.8: 1.5: 1.5: 0.2: 55, 96.8: 2.0: 1.0: 0.2: 6, etc.
[0064] According to a second aspect of the present invention, a method for preparing the above-mentioned lithium manganese iron phosphate composite positive electrode slurry is also provided, comprising the following steps:
[0065] (a) mixing a binder and a solvent to obtain a mixed glue solution;
[0066] (b) adding a conductive agent and a dispersant to the mixed adhesive to obtain a conductive adhesive;
[0067] (c) adding an active material formed by mixing lithium manganese iron phosphate and a ternary material into the conductive glue to mix and disperse the mixture, thereby obtaining a lithium manganese iron phosphate composite positive electrode slurry.
[0068] The present invention adopts a multi-step dispersion process with low solid content, avoids the kneading step with high solid content, controls the solid content of the added slurry during the homogenization process, ensures the uniform dispersion of each component, and avoids the wear of the equipment and the introduction of metal foreign matter caused by the high solid content slurry. At the same time, considering the small particles of conductive carbon black SP and the characteristics of multi-walled carbon nanotubes that are difficult to disperse and easy to agglomerate, the preparation method of the present invention adopts a method of dispersing the conductive agent separately to avoid uneven dispersion of the conductive agent and affect the battery performance.
[0069] As an optional embodiment of the present invention, in step (a), the binder and the solvent are first stirred and mixed at a low speed, and then dispersed at a high speed to obtain a mixed adhesive solution.
[0070] First use low-speed stirring to mix, and then high-speed dispersion. The purpose is to avoid the splashing of binder powder at high speed and insufficient contact with the solvent, resulting in uneven dispersion.
[0071] As an optional embodiment of the present invention, in step (a), the stirring speed of low-speed stirring and mixing is 20-40rpm (for example, 20rpm, 25rpm, 30rpm, 35rpm or 40rpm, etc.), the stirring time is 5-15min (for example, 5min, 10min or 15min, etc.), the dispersion linear velocity of high-speed dispersion is 12-18m / s (for example, 12m / s, 15m / s, 17m / s or 18m / s, etc.), and the dispersion time is 2.5-3.5h (for example, 2.5h, 3.0h or 3.5h, etc.).
[0072] As an optional embodiment of the present invention, in step (b), the conductive agent and the dispersant are added to the mixed glue solution, first stirred and mixed at a low speed, and then dispersed at a high speed to obtain the conductive glue solution.
[0073] First use low-speed stirring to mix, and then high-speed dispersion. The purpose is to avoid the conductive agent powder splashing at high speed and not fully contacting the mixed glue, resulting in uneven dispersion.
[0074] As an optional embodiment of the present invention, in step (b), the stirring speed of low-speed stirring and mixing is 20-40rpm (for example, 20rpm, 25rpm, 30rpm, 35rpm or 40rpm, etc.), the stirring time is 5-15min (for example, 5min, 10min or 15min, etc.), the dispersion linear speed of high-speed dispersion is 12-18m / s (for example, 12m / s, 15m / s, 17m / s or 18m / s, etc.), and the dispersion time is 0.5-1.5h (for example, 0.5h, 1.0h or 1.5h, etc.).
[0075] As an optional embodiment of the present invention, in step (b), the solid content of the conductive adhesive is 7-10% (for example, 7%, 8%, 9% or 10%, etc.).
[0076] As an optional embodiment of the present invention, in step (c), the active material formed by mixing lithium manganese iron phosphate and the ternary material is added to the conductive glue and first stirred and mixed at a low speed, and then dispersed at a high speed.
[0077] First use low-speed stirring to mix, and then high-speed dispersion. The purpose is to avoid the active material powder splashing at high speed and not fully contacting with the conductive glue, resulting in uneven dispersion.
[0078] As an optional embodiment of the present invention, in step (c), the stirring speed of low-speed stirring and mixing is 20-40rpm (for example, 20rpm, 25rpm, 30rpm, 35rpm or 40rpm, etc.), the stirring time is 5-15min (for example, 5min, 10min or 15min, etc.), the dispersion linear speed of high-speed dispersion is 12-18m / s (for example, 12m / s, 15m / s, 17m / s or 18m / s, etc.), and the dispersion time is 2-3h (for example, 2.0h, 2.5h or 3.0h, etc.).
[0079] According to a third aspect of the present invention, there is also provided a manganese iron phosphate lithium composite positive electrode sheet, comprising a current collector and an active coating disposed on the surface of the current collector;
[0080] The above-mentioned active coating is made of the lithium iron manganese phosphate composite positive electrode slurry provided by the first aspect of the present invention or the lithium iron manganese phosphate composite positive electrode slurry prepared by the preparation method provided by the second aspect of the present invention.
[0081] In view of the advantages of the above-mentioned lithium iron manganese phosphate composite positive electrode slurry provided by the present invention, the positive electrode sheet prepared therefrom has good softness, high compaction density and peeling strength, and low membrane resistance.
[0082] According to a fourth aspect of the present invention, there is also provided a lithium-ion battery comprising the lithium manganese iron phosphate composite positive electrode sheet provided by the third aspect of the present invention.
[0083] In view of the advantages of the above-mentioned lithium iron manganese phosphate composite positive electrode sheet provided by the present invention, the lithium ion battery containing the same has more excellent electrochemical performance.
[0084] The present invention is further described in detail below in conjunction with specific embodiments and comparative examples. It should be noted that the specific raw material information used in the following embodiments and comparative examples is as follows: multi-walled carbon nanotube slurry doped with graphene, purchased from the manufacturer Jiangsu Tiannai, brand LB156-42, the total solid content of the slurry is 5.6±0.2%, the total solid content of graphene and multi-walled carbon nanotubes in the slurry is 4.0±0.15%, the average tube diameter of the multi-walled carbon nanotubes is 5-11nm, and the solid content of the dispersant in the slurry is 1.6±0.05%; conductive carbon black SP is purchased from the manufacturer Swiss Temeco, with a particle size of 30-50nm.
[0085] Example 1
[0086] This embodiment provides a lithium manganese iron phosphate composite positive electrode slurry, including the following raw materials: active material, conductive agent, binder, dispersant and solvent, the mass ratio of active material, conductive agent, binder, dispersant and solvent is 96:1.9:2.0:0.1:50;
[0087] Among them, the active materials include lithium iron manganese phosphate (average particle size 0.75nm) and ternary materials (eight series NCM, average particle size 13nm), and the mass ratio of lithium iron manganese phosphate to ternary materials is 7:3;
[0088] The conductive agent includes conductive carbon black SP and multi-walled carbon nanotube slurry doped with graphene, and the mass ratio of the conductive carbon black SP to the multi-walled carbon nanotube slurry doped with graphene is 1.4:0.5;
[0089] The binder includes PVDF binder A and PVDF binder B, the compounding mass ratio of PVDF binder A and PVDF binder B is 3:1, PVDF binder A is HSV900 with a molecular weight of 800,000, and PVDF binder B is Solvay 5130 with a molecular weight of 1 million;
[0090] The dispersant is a high molecular polymer with an anchoring group and a polyester-type soluble long-chain structure (brand name: Haofei HFF-2968);
[0091] The solvent was NMP.
[0092] This embodiment also provides a method for preparing a lithium manganese iron phosphate composite positive electrode slurry, comprising the following steps:
[0093] (a) PVDF binder A and PVDF binder B were dispersed in NMP solvent, firstly stirred and mixed at a low speed of 30 rpm for 10 min, then dispersed at a high speed of 15 m / s for 180 min, and vacuumized at -90 kPa to obtain a mixed adhesive solution with a solid content of 6%;
[0094] (b) adding a conductive agent (conductive carbon black SP and graphene-doped multi-walled carbon nanotube slurry) to the above mixed glue, and adding a formulated amount of dispersant, first stirring and mixing at a low speed of 30 rpm for 10 min, and then dispersing at a high speed, with a dispersion line speed of 15 m / s and a dispersion time of 60 min, and evacuating to -90 kPa to obtain a conductive glue with a solid content of 8%;
[0095] (c) The lithium manganese iron phosphate and ternary materials in the formula are stirred and mixed evenly to form an active substance, and the active substance is added to the above conductive glue and stirred and mixed at a low speed of 30 rpm for 10 min, and then dispersed at a high speed with a dispersion line speed of 15 m / s and a dispersion time of 180 min, and vacuumed to -90 kPa to obtain a lithium manganese iron phosphate composite positive electrode slurry.
[0096] Example 2
[0097] This embodiment provides a lithium iron manganese phosphate composite positive electrode slurry. Except for adjusting the mass ratio of lithium iron manganese phosphate and ternary material in the active material from 7:3 to 9:1, the types and amounts of other raw materials are the same as those in Example 1.
[0098] In the preparation method of the lithium manganese iron phosphate composite positive electrode slurry of this embodiment, except that the mass ratio of lithium manganese iron phosphate and ternary material added in step (c) is adjusted from 7:3 to 9:1, the remaining steps and process parameters are the same as those in Example 1.
[0099] Example 3
[0100] This embodiment provides a lithium manganese iron phosphate composite positive electrode slurry. Except for adjusting the mass ratio of lithium manganese iron phosphate and ternary material in the active material from 7:3 to 8:2, the types and amounts of other raw materials are the same as those in Example 1.
[0101] In the preparation method of the lithium manganese iron phosphate composite positive electrode slurry of this embodiment, except that the mass ratio of lithium manganese iron phosphate and ternary material added in step (c) is adjusted from 7:3 to 8:2, the remaining steps and process parameters are the same as those in Example 1.
[0102] Example 4
[0103] This embodiment provides a lithium manganese iron phosphate composite positive electrode slurry. Except that the compounding mass ratio of PVDF binder A and PVDF binder B is adjusted from 3:1 to 1:3, the types and amounts of other raw materials are the same as those in Example 1.
[0104] In the preparation method of the lithium manganese iron phosphate composite positive electrode slurry of this embodiment, except that the compounding mass ratio of PVDF binder A and PVDF binder B in step (a) is adjusted from 3:1 to 1:3, the remaining steps and process parameters are the same as those in Example 1.
[0105] Example 5
[0106] This embodiment provides a lithium manganese iron phosphate composite positive electrode slurry. Except that the compounding mass ratio of PVDF binder A and PVDF binder B is adjusted from 3:1 to 1:1, the types and amounts of other raw materials are the same as those in Example 1.
[0107] In the preparation method of the lithium manganese iron phosphate composite positive electrode slurry of this embodiment, except that the compounding mass ratio of PVDF binder A and PVDF binder B in step (a) is adjusted from 3:1 to 1:1, the remaining steps and process parameters are the same as those in Example 1.
[0108] Example 6
[0109] This embodiment provides a lithium manganese iron phosphate composite positive electrode slurry. Except that the specific type of PVDF binder A is replaced by an equal amount of HSV1810 (molecular weight of about 700,000) from HSV900, the other raw material types, amounts and preparation methods are the same as those in Example 1.
[0110] In the preparation method of the lithium manganese iron phosphate composite positive electrode slurry of this comparative example, except that the specific type of PVDF binder A in step (a) is replaced by an equal amount of HSV1810 (molecular weight of about 700,000) from HSV900, the remaining steps and process parameters are the same as those in Example 1.
[0111] Example 7
[0112] This embodiment provides a lithium manganese iron phosphate composite positive electrode slurry, including the following raw materials: an active material, a conductive agent, a binder, a dispersant and a solvent, wherein the mass ratio of the active material, the conductive agent, the binder, the dispersant and the solvent is 96.8:1.5:1.5:0.2:55;
[0113] Among them, the active materials include lithium iron manganese phosphate (average particle size 0.75nm) and ternary materials (eight series NCM, average particle size 13nm), and the mass ratio of lithium iron manganese phosphate to ternary materials is 8:2;
[0114] The conductive agent includes conductive carbon black SP and multi-walled carbon nanotube slurry doped with graphene, and the mass ratio of the conductive carbon black SP to the multi-walled carbon nanotube slurry doped with graphene is 1:1;
[0115] The binder includes PVDF binder A and PVDF binder B, the compounding mass ratio of PVDF binder A and PVDF binder B is 1:2, PVDF binder A is HSV900 with a molecular weight of 800,000, and PVDF binder B is Solvay 5130 with a molecular weight of 1.1 million;
[0116] The dispersant is a high molecular polymer with an anchoring group and a polyester-type soluble long-chain structure (brand name: Haofei HFF-2968);
[0117] The solvent was NMP.
[0118] This embodiment also provides a method for preparing a lithium manganese iron phosphate composite positive electrode slurry, comprising the following steps:
[0119] (a) PVDF binder A and PVDF binder B were dispersed in NMP solvent, firstly stirred and mixed at a low speed of 40 rpm for 5 min, and then dispersed at a high speed of 17 m / s for 150 min, and vacuumed at -90 kPa to obtain a mixed adhesive solution with a solid content of 6%;
[0120] (b) adding the conductive carbon black SP and the graphene-doped multi-walled carbon nanotube slurry to the above mixed glue, and adding the formulated amount of dispersant, first stirring and mixing at a low speed of 40 rpm for 5 min, and then dispersing at a high speed, with a dispersion line speed of 17 m / s and a dispersion time of 90 min, and evacuating to -90 kPa to obtain a conductive glue with a solid content of 6.5%;
[0121] (c) The lithium manganese iron phosphate and ternary materials in the formula are stirred and mixed evenly to form an active substance, and the active substance is added to the above conductive glue and stirred and mixed at a low speed of 40 rpm for 5 min, and then dispersed at a high speed with a dispersion line speed of 17 m / s and a dispersion time of 150 min, and vacuumed to -90 kPa to obtain a lithium manganese iron phosphate composite positive electrode slurry.
[0122] Comparative Example 1
[0123] The present comparative example provides a lithium iron manganese phosphate composite positive electrode slurry, except that the multi-walled carbon nanotube slurry doped with graphene in the conductive agent is replaced with conductive carbon black SP, that is, the conductive agent of the present comparative example contains only conductive carbon black SP, and the amount of the conductive agent conductive carbon black SP is equal to the total amount of graphene, multi-walled carbon nanotubes and conductive carbon black SP in the multi-walled carbon nanotube slurry doped with graphene in Example 1, and the types and amounts of other raw materials are the same as those in Example 1.
[0124] In the preparation method of the lithium manganese iron phosphate composite positive electrode slurry of this comparative example, except that the multi-walled carbon nanotube slurry doped with graphene in the conductive agent is replaced with conductive carbon black SP in step (b), the remaining steps and process parameters are the same as those in Example 1.
[0125] Comparative Example 2
[0126] This comparative example provides a lithium iron manganese phosphate composite positive electrode slurry, except that the multi-walled carbon nanotube slurry doped with graphene in the conductive agent is replaced by single-walled carbon nanotubes (undoped with graphene), and the amount of single-walled carbon nanotubes is equal to the total amount of graphene and multi-walled carbon nanotubes in the multi-walled carbon nanotube slurry doped with graphene, and the other raw material types and amounts are the same as those in Example 1.
[0127] In the preparation method of the lithium manganese iron phosphate composite positive electrode slurry of this comparative example, except that the multi-walled carbon nanotube slurry doped with graphene in the conductive agent in step (b) is replaced with single-walled carbon nanotubes (undoped with graphene), the remaining steps and process parameters are the same as those in Example 1.
[0128] Comparative Example 3
[0129] This comparative example provides a lithium iron manganese phosphate composite positive electrode slurry, except that no dispersant is added to the lithium iron manganese phosphate composite positive electrode slurry, and the mass ratio of the active material, the conductive agent, the binder and the solvent is 96:2.0:2.0:50, the mass ratio of the conductive carbon black SP and the multi-walled carbon nanotubes doped with graphene in the conductive agent is 1.5:0.5, and the types and amounts of other raw materials are the same as those in Example 1.
[0130] In the preparation method of the lithium manganese iron phosphate composite positive electrode slurry of this comparative example, except that no dispersant is added to the mixed glue solution in step (b), the remaining steps and process parameters are the same as those in Example 1.
[0131] Comparative Example 4
[0132] This comparative example provides a lithium iron manganese phosphate composite positive electrode slurry. Except that the type of dispersant in the lithium iron manganese phosphate composite positive electrode slurry is replaced by an equal amount of polyvinyl pyrrolidone (PVP) from HFF2968, the types and amounts of other raw materials are the same as those in Example 1.
[0133] In the preparation method of the lithium manganese iron phosphate composite positive electrode slurry of this comparative example, except that the dispersant HFF2968 in the mixed colloid solution in step (b) is replaced by an equal amount of polyvinyl pyrrolidone (PVP), the remaining steps and process parameters are the same as those in Example 1.
[0134] Comparative Example 5
[0135] This comparative example provides a lithium manganese iron phosphate composite positive electrode slurry, except that only PVDF binder A is used as the binder, and the total amount of PVDF binder A in this comparative example is the same as the total amount of PVDF binder A and PVDF binder B in Example 1, and the types and amounts of other raw materials are the same as those in Example 1.
[0136] In the preparation method of the lithium manganese iron phosphate composite positive electrode slurry of this comparative example, except that the PVDF binder B is replaced by an equal amount of PVDF binder A in step (a), the remaining steps and process parameters are the same as those in Example 1.
[0137] Comparative Example 6
[0138] This comparative example provides a lithium manganese iron phosphate composite positive electrode slurry, except that only PVDF binder B is used as the binder, and the total amount of PVDF binder B in this comparative example is equal to the total amount of PVDF binder A and PVDF binder B in Example 1, and the types and amounts of other raw materials are the same as those in Example 1.
[0139] In the preparation method of the lithium manganese iron phosphate composite positive electrode slurry of this comparative example, except that the PVDF binder A is replaced with an equal amount of PVDF binder B in step (a), the remaining steps and process parameters are the same as those in Example 1.
[0140] Comparative Example 7
[0141] This comparative example provides a lithium manganese iron phosphate composite positive electrode slurry, and the specific raw material composition is the same as that of Example 1.
[0142] The preparation method of the lithium manganese iron phosphate composite positive electrode slurry in this comparative example comprises the following steps:
[0143] (a) According to the composition of lithium manganese iron phosphate composite positive electrode slurry, all the raw materials in the formula amount are added into a double planetary beater and stirred for 3 hours to obtain a slurry;
[0144] (b) The slurry was put into a high-speed disperser with a dispersion line speed of 15 m / s and a dispersion time of 180 min. The vacuum was drawn to -90 kPa to obtain a manganese iron phosphate lithium composite positive electrode slurry.
[0145] In order to compare the technical effects of the above embodiments and comparative examples, the following experimental examples are specially designed.
[0146] Experimental Example 1
[0147] (1) The viscosity (25±3° C.) and solid content of the lithium manganese iron phosphate composite positive electrode slurry obtained in each embodiment and comparative example were tested at different times. The specific results are shown in Table 1.
[0148] Table 1
[0149]
[0150]
[0151] It can be seen from the data in Table 1 that the 24h viscosity change of the lithium manganese iron phosphate composite positive electrode slurry provided by each embodiment of the present invention is small, and the solid content is high.
[0152] Specifically, Examples 1-5 are all control experiments of Example 1. Among them, Examples 2 and 3 mainly investigate the effect of the mass ratio of lithium iron manganese phosphate and ternary materials in the active material on the performance of lithium iron manganese phosphate composite positive electrode slurry. It can be seen from the data of Examples 2 and 3 that by increasing the proportion of lithium iron manganese phosphate, the viscosity of the slurry can be rebounded and the solid content can be reduced. This is mainly because the lithium iron manganese phosphate particles are small and have a large specific surface area. The particles are easy to agglomerate and absorb water, resulting in slurry instability and easy viscosity rebound. Examples 4 and 5 mainly investigate the effect of the compounding mass ratio of PVDF binder A and PVDF binder B on the performance of lithium iron manganese phosphate composite positive electrode slurry. It can be seen from the data in Table 1 that due to the poor anti-gelation properties of the high molecular weight PVDF binder B, the increase in its usage ratio will significantly increase the viscosity of the slurry after standing for 24 hours, and the overall solid content will be reduced accordingly.
[0153] Comparative Examples 1-6 are also comparative experiments of Example 1. Among them, Comparative Examples 1 and 2 are both to investigate the influence of specific types of conductive agents on slurry performance. Compared with Example 1, when the conductive agent only uses conductive carbon black SP, the slurry performance and solid content changes are not obvious. When the conductive agent only uses carbon nanotubes, the slurry viscosity rebounds and the solid content decreases. This is mainly because the carbon nanotubes themselves are poorly dispersed and easy to agglomerate, especially single-walled carbon nanotubes. At the same time, carbon nanotube powders generally have many modified groups, and excessive addition will affect the stability of the slurry. Comparative Examples 3 and 4 are both to investigate the influence of the amount or type of dispersant on slurry performance. When the specific type of dispersant of the present invention is not added, the raw materials in the manganese iron phosphate lithium composite positive electrode slurry are unevenly dispersed, the agglomeration is more serious, the slurry viscosity rebounds significantly, and the solid content is low and unstable. When the binder uses the traditional binder PVP, the viscosity rebound of the manganese iron phosphate lithium composite positive electrode slurry is not obvious, and the solid content is moderate, but the overall effect is still slightly worse than Example 1. Comparative Examples 5 and 6 investigate the effect of a single type of PVDF binder (PVDF binder A or PVDF binder B) on the slurry performance. When a single low molecular weight PVDF binder (PVDF binder A) is used, the solid content of the positive electrode slurry is relatively low. When a single high molecular weight PVDF binder (PVDF binder B) is used, due to its poor anti-gel properties, the viscosity of the positive electrode slurry rebounds significantly. Comparative Example 7 investigates the effect of the homogenization process on the slurry performance. Comparative Example 7 does not use a step-by-step homogenization process. All raw materials are stirred together for homogenization. The viscosity of the prepared slurry rebounds, and the solid content is low and unstable, and the slurry will settle. This is because various powders, especially high molecular weight PVDF binder powders, will agglomerate together, and it is difficult for double planetary stirring to break up these small particles, resulting in poor dispersion, unstable slurry and easy sedimentation.
[0154] (2) The lithium manganese iron phosphate composite positive electrode slurry obtained in each embodiment and comparative example is made into a pole piece. The specific preparation method is as follows: the positive electrode slurry is evenly sprayed on the carbon-coated aluminum foil through an extrusion coater, and then passed through an oven at a coating speed of 5-8m / s to obtain a dried single-sided positive electrode sheet, and then double-coated on the second side to obtain a positive electrode sheet. The oven temperature is 100-105°C, and the single-sided surface density is controlled to be 190±1g / m 2 , double-sided surface density control 380±2g / m 2 After the positive electrode sheet is coated, it is rolled by a rolling device to obtain a positive electrode sheet with a thickness of 158±2μm, and then cut and trimmed to obtain a positive electrode sheet of suitable size.
[0155] The performance of the electrode sheets made in each embodiment and comparative example was tested. The membrane resistance test was performed using a Yuanneng Technology electrode sheet resistance meter; the test pressure was set to 20Mpa, the pressure holding time was 10s, the end face of the test block was wiped with alcohol, and the electrode sheet was placed on the test platform. The test was started to obtain the electrode sheet resistance. Three groups of parallel samples were tested for each sample, and the test block terminal was wiped with alcohol before each sample was tested.
[0156] The compaction of the electrode is calculated theoretically. The coated electrode is subjected to different pressures through a rolling device to obtain electrode sheets of different thicknesses. The equipment is equipped with a thickness detector to monitor the thickness of the rolling process online. If the electrode sheet after rolling is folded twice and then breaks or is light-transmissive, it indicates that the compaction is too large and needs to be reduced. Pole sheet compaction = electrode sheet surface density / (rolling thickness-foil thickness).
[0157] The peel strength test was conducted in accordance with GB / T 2792-2014 Adhesive Tape Peel Strength Test Method. The specific results are shown in Table 2.
[0158] Table 2
[0159]
[0160] From the diaphragm resistance data in Table 2, it can be seen that compared with Example 1, the diaphragm resistance of Comparative Example 1, which only adds conductive carbon black, is significantly increased, which also shows that the addition of a certain amount of multi-walled carbon nanotubes doped with graphene can significantly improve the diaphragm resistance of the electrode. Comparative Example 2 uses single-walled carbon nanotubes, Comparative Example 3 does not add a dispersant, and Comparative Example 6 only uses the easy-to-gel PVDF binder B. The slurries prepared in these comparative examples are not evenly dispersed, resulting in a certain increase in diaphragm resistance.
[0161] It can be seen from the electrode compaction data that in Example 2, the compaction density is significantly reduced due to the reduction in the ternary ratio, and in the other comparative examples, the electrode surface is abnormal due to the poor dispersion of the slurry, and the compaction density is reduced to varying degrees.
[0162] At the same time, it was found that in Comparative Example 5, which only used low molecular weight PVDF binder A, the peel strength of the pole piece was significantly reduced, while in Comparative Example 6, which only used high molecular weight PVDF binder B, the peel strength of the pole piece was significantly increased, but there were more abnormalities on the surface of the pole piece. Comparative Example 7 did not adopt the process of step-by-step feeding, but all the raw materials were stirred together, and the pole piece showed particles, cracks and poor conductivity. This is because the powder was not gradually dispersed evenly in the early stage, and it was difficult to disperse it after agglomeration, especially the high molecular weight PVDF binder B and the conductive agent.
[0163] Experimental Example 2
[0164] The lithium iron manganese phosphate composite positive electrode slurry obtained in each embodiment and comparative example is made into a positive electrode sheet, and a lithium ion battery is assembled with a negative electrode sheet. The specific manufacturing method of the lithium ion battery is as follows:
[0165] Positive electrode sheet: The positive electrode slurry is obtained by using the materials and proportions described above in each embodiment and comparative example. The slurry is coated on the surface of carbon-coated aluminum foil, and then baked, rolled, slit and cut to obtain the positive electrode sheet;
[0166] Negative electrode sheet: graphite: conductive agent (SP): thickener (CMC, sodium carboxymethyl cellulose): binder (SBR, styrene-butadiene latex): solvent (deionized water) are prepared into a negative electrode slurry in a ratio of 96.5:0.5:1.2:1.8:85; the slurry is sprayed on a copper foil by an extrusion coater, and then baked in a multi-section oven, and then cold pressed by a roller press, and then cut and cut to obtain a negative electrode sheet;
[0167] Assembly: Place the cut positive and negative electrode sheets on the stacking machine, and stack them together in the order of negative electrode sheet, separator, and positive electrode sheet to obtain a bare core package; weld the positive and negative electrode ears of the core package respectively and then wrap it with aluminum-plastic film, and finally perform top and side sealing to the dry battery cell;
[0168] Liquid injection, formation and capacity separation: the battery cell is baked, the moisture content of the positive electrode is ≤200ppm, and the moisture content of the negative electrode is ≤150ppm; liquid injection is carried out after the moisture content is qualified. After liquid injection, the battery cell is subjected to high-temperature activation, formation, secondary sealing and capacity separation to obtain the finished battery cell.
[0169] The rate performance and cycle performance of the lithium ion batteries prepared in each embodiment and comparative example were tested, and the specific results are shown in Table 3.
[0170] 3C rate performance test: Under 25±3℃ conditions, the battery was charged and discharged using a 1C charge / 1C discharge pattern, and the capacity was C0. The battery was charged and discharged using a 1C charge / 3C discharge pattern, and the capacity was C1. The 3C rate discharge retention rate was C1 / C0. Similarly, the battery was charged and discharged using a 3C charge / 1C discharge pattern, and the capacity was C2. The 3C rate charge retention rate was C2 / C0.
[0171] Cycle performance test: Normal temperature cycle is carried out at 25±3℃, and high temperature cycle is carried out at 45±3℃; the battery cell is charged and discharged according to the charge and discharge system of 1C charge / 1C discharge, and is placed for 30 minutes after the charge and discharge. One full charge and discharge is recorded as one cycle, and the charge and discharge steps are repeated until the capacity is less than or equal to 80% of the initial capacity.
[0172] Table 3
[0173]
[0174]
[0175] It can be seen from the rate performance data in Table 3 that the rate performance of the lithium-ion battery prepared in each embodiment of the present invention is improved to a certain extent by adding a certain proportion of multi-walled carbon nanotubes doped with graphene, increasing the proportion of ternary materials, and mixing PVDF binders of different molecular weights. However, due to the poor performance of the slurry in the early stage and the poor performance of the subsequent pole piece, the rate performance of the battery cell is weakened to a certain extent in Comparative Examples 2, 3 and 6.
[0176] Similarly, the cycle performance of each embodiment of the present invention also has obvious advantages, and the capacity remains relatively stable, while the cycle performance of the comparative examples is weakened to varying degrees due to defects in the electrode performance. Specifically, since comparative example 1 only uses conductive carbon black as a conductive agent, its electrode impedance is large, and the normal temperature cycle performance and high temperature cycle performance are poor; and comparative examples 5 and 6, since only one PVDF binder is used, either the electrode peeling strength is poor, resulting in the shedding of active materials, or the slurry dispersion is poor, resulting in poor electrode performance and then poor battery cell cycle performance. Comparative example 7 has poor conductivity and poor rate performance of the subsequent battery due to poor slurry dispersion and poor electrical properties of the electrode in the early stage; at the same time, the expansion of the electrode during the cycle causes the shedding of powder, which further deteriorates the cycle performance.
[0177] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.
Claims
1. A lithium manganese iron phosphate composite positive electrode slurry, characterized in that: It includes the following raw materials: active material, conductive agent, binder, dispersant and solvent; The active material includes lithium manganese iron phosphate and ternary material, and the mass ratio of lithium manganese iron phosphate to the ternary material is (7-9): (3-1); The conductive agent includes conductive carbon black SP and multi-walled carbon nanotubes; The binder includes a PVDF binder A with a molecular weight of 600,000-800,000 and a PVDF binder B with a molecular weight of 900,000-1.2 million; The dispersant includes a high molecular weight polymer having an anchoring group and a soluble long chain structure.
2. The lithium iron manganese phosphate composite positive electrode slurry according to claim 1, characterized in that: The mass ratio of the conductive carbon black SP and the multi-walled carbon nanotubes in the conductive agent is (1-2): (0.5-1); And / or, the multi-walled carbon nanotubes are graphene-doped multi-walled carbon nanotube slurry; And / or, the mass ratio of PVDF binder A to PVDF binder B in the binder is (3-1):(1-3).
3. The lithium iron manganese phosphate composite positive electrode slurry according to claim 1, characterized in that: The anchoring group in the dispersant comprises at least one of a hydroxyl group, a carboxylic acid group, an amino group, an amide group, and a phosphate group; And / or, the soluble long chains in the dispersant include polyester soluble long chains.
4. The lithium manganese iron phosphate composite positive electrode slurry according to any one of claims 1 to 3, characterized in that: The ternary material includes high nickel polycrystalline eight-series NCM and nine-series NCM; and / or, the solvent comprises N-methylpyrrolidone; And / or, the mass ratio of the active material, conductive agent, binder, dispersant and solvent is (95-97): (1.5-2.5): (1.5-2.5): (0.1-0.2): (50-65).
5. The method for preparing the lithium manganese iron phosphate composite positive electrode slurry according to any one of claims 1 to 4, characterized in that: The following steps are involved: (a) mixing and dispersing a binder and a solvent to obtain a mixed glue solution; (b) adding a conductive agent and a dispersant to the mixed adhesive solution and mixing and dispersing the mixed adhesive solution to obtain a conductive adhesive solution; (c) adding an active material formed by mixing lithium manganese iron phosphate and a ternary material into the conductive glue to mix and disperse the mixture, thereby obtaining a lithium manganese iron phosphate composite positive electrode slurry.
6. The method for preparing the lithium iron manganese phosphate composite positive electrode slurry according to claim 5, characterized in that: In step (a), the binder and the solvent are first stirred and mixed at a low speed, and then dispersed at a high speed to obtain a mixed adhesive solution; Preferably, in step (a), the stirring speed of the low-speed stirring and mixing is 20-40 rpm, the stirring time is 5-15 min, and the dispersion linear speed of the high-speed dispersion is 12-18 m / s, and the dispersion time is 2.5-3.5 h; Preferably, in step (a), the solid content of the mixed glue solution is 4-8%.
7. The method for preparing the lithium iron manganese phosphate composite positive electrode slurry according to claim 5, characterized in that: In step (b), a conductive agent and a dispersant are added to the mixed glue solution, first stirred and mixed at a low speed, and then dispersed at a high speed to obtain a conductive glue solution; Preferably, in step (b), the stirring speed of the low-speed stirring and mixing is 20-40 rpm, the stirring time is 5-15 min, and the dispersion linear speed of the high-speed dispersion is 12-18 m / s, and the dispersion time is 0.5-1.5 h; Preferably, in step (b), the solid content of the conductive adhesive is 7-10%.
8. The method for preparing the lithium iron manganese phosphate composite positive electrode slurry according to any one of claims 5 to 7, characterized in that: In step (c), the active material formed by mixing lithium manganese iron phosphate and the ternary material is added to the conductive glue solution, first stirred and mixed at a low speed, and then dispersed at a high speed; Preferably, in step (c), the stirring speed of the low-speed stirring and mixing is 20-40 rpm, the stirring time is 5-15 min, and the dispersion linear speed of the high-speed dispersion is 12-18 m / s, and the dispersion time is 2-3 h.
9. A lithium manganese iron phosphate composite positive electrode sheet, characterized in that: It includes a current collector and an active coating disposed on the surface of the current collector; The active coating is made of the lithium iron manganese phosphate composite positive electrode slurry described in any one of claims 1-4 or the lithium iron manganese phosphate composite positive electrode slurry prepared by the preparation method described in any one of claims 5-8.
10. A lithium ion battery, characterized in that: A lithium manganese iron phosphate composite positive electrode sheet comprising the method of claim 9.
Citation Information
Patent Citations
Positive electrode material and battery cell structure
CN114583157A
Lithium battery and power equipment comprising same
CN115911510A
Lithium manganese iron phosphate positive electrode slurry, positive electrode plate and preparation method of lithium manganese iron phosphate positive electrode slurry and positive electrode plate
CN116864605A
Negative electrode material, negative electrode plate, and electrochemical apparatus and electronic apparatus containing such negative electrode plate
US20230343943A1